First, factor out a pir from each term in the right side of the equation:
S = pir(r + l)
Next, divide each side of the equation by color(red)(pir) to eliminate the coefficient while keeping the equation balanced:
S/color(red)(pir) = (pir(r + l))/color(red)(pir)
S/(pir) = (color(red)(cancel(color(black)(pir)))(r + l))/cancel(color(red)(pir))
S/(pir) = r + l
Now, subtract color(red)(r) from each side of the equation to solve for l:
-color(red)(r) + S/(pir) = -color(red)(r) + r + l
-r + S/(pir) = 0 + l
-r + S/(pir) = l
l = -r + S/(pir)
If you want the right side of the equation to be over a common denominator you can multiply -r by (pir)/(pir) giving:
l = ((pir)/(pir) xx -r) + S/(pir)
l = (-pir^2)/(pir) + S/(pir)
l = (-pir^2 + S)/(pir)
l = (S - pir^2)/(pir)
The solution is: l = -r + S/(pir) or l = (S - pir^2)/(pir)